What are the home care needs of Chinese healthcare workers: a latent class analysis - Zhou, Luling; Liu, Suzhen; Li, Hang (Frontiers in Public Health, 2024)
The ageing population has led to a surge in demand for home care, which has developed rapidly in China in recent years.However, there has been less empirical research into the needs of healthcare workers about providing home care. The purpose of this study was to explore the latent classes of healthcare workers' needs in primary health care institutions and to identify associated factors.Methods: From August 2021 to June 2022, a convenience sampling method was adopted to conduct a questionnaire survey on the workers of 62 primary healthcare institutions in Sichuan Province. Latent class analysis was used to categorize home care needs by Mplus 8.3. Multinomial logistic regression analysis was adopted to explore the influencing factors using SPSS 25.0.Results: A total of 1152 healthcare workers were included in the study. Their needs for home care were classified into four latent classes: overall high need group (18.0%); overall low need group (34.8%); high training and low support need group (29.9%), and the high security and low training need group (17.3%). The factors influencing the different need categories included working area, professional title, role of medical workers, had participated in training about home care, and feelings about home care, with Class 1 as the reference group.Our findings indicate that primary healthcare workers have multifaceted needs for providing home care. Paying attention to their diverse needs can help optimise home care and enhance service capacity. Exploring the factors affecting needs can provide targeted support to healthcare workers to ensure the quality and continuity of home care services.